Increasing vegetable intake 400 g/day can control body weight and lipid profile in overweight hyperlipidemia menopausal women - Indri Kartiko Sari; Diah Mulyawati Utari; Sumiko Kamoshita; Dwi Oktaviana; Seigo Sakai; Hiroshi Nishiyama; Yasunobu Masuda; Shigeru Yamamoto (SAGE Publishing, 2020)
Background: Indonesia suffers growing health problems like obesity, diabetes, and other metabolic syndromes with dietary habit as one of risk factors. To control the lipid and glycaemic profile, high fibre intake has been recommended. This study administered 400g/day vegetable intake with its fiber contents and observed the effects in lipid profile and glycaemic control. Design: A parallel study of 30 pairs of menopausal women match paired in overweight, menopause, hyperlipidaemia, age, etc randomly divided into two groups (vegetable and control). The baseline data obtained from questionnaire and preliminary blood-withdrawn of consented participants, then matched the characteristics included the results of lipid profile and glycated albumin. The administration was conducted for 21days by providing 400g/day of vegetable to the vegetable group subjects. Nutrition assessments were conducted at the baseline, middle, and final period. The data were analysed by using the unpaired and paired t-test. Results: Significant results (p<0.05) were seen in biochemical variables in the lipid profile of total cholesterol, LDL cholesterol, and HDL cholesterol and body weight and BMI within the vegetable group. Significant results for the same variables were shown between vegetable and control group at the final data (p<0.05). The nutrition assessments result showed significances (p<0.05) within vegetable group and between two groups on the final data. After 21 days, significant decreases were found on the intakes of energy, lipids, carbohydrates (p<0.05), while vegetable intake and fiber intake showed significant increases (p<0.05). Conclusion: These data suggest that maintaining a healthy diet of 400 g/d vegetable can be effective in weight management and lipid profile control.